Variabilidad genética de poblaciones en cautiverio de Crocodylus moreletii (Crocodylia: Crocodylidae) mediante el uso de marcadores microsatelitales. - Serna-Lagunes, Ricardo; González, Dolores; Díaz-Rivera, Pablo (Revista de Biología Tropical, 2012)
Crocodylus moreletii, an extinction threatened species, represents an emblem for tropical ecosystems in Mexico. Surprisingly, there is a lack of information about their genetic constitution, which should be evaluated for a proper management ex situ and for making decisions on the release of crocodiles into natural habitats. The aim of this study was to characterize and compare the genetic variability of four populations of C. moreletii (two wild versus two born ex situ). Through PCR were amplified seven microsatellite polymorphic loci, however a heterozygote deficit, diminished by the presence of null alleles, was found in the populations (average HO=0.02). The AMOVA indicated that the highest proportion of genetic variability is within populations, and a limited genetic differentiation among populations (average FST=0.03), probably due to high inbreeding index (average FIS=0.97). When comparing the genetic variability between and within other crocodilian species, we found that in C. moreletii is well below those reported. We concluded that the limited genetic variability in ex situ born populations is probably due to a founder effect derived from the social structure of their progenitors, and by the bottleneck effect, inferred by the limited effective population size, that historically characterizes their natural distribution in wild populations.